2022
DOI: 10.1021/acscentsci.2c00340
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering of Ceria Nanocrystals for Enhanced Catalysis via a High-Entropy Oxide Strategy

Abstract: Introducing transition-metal components to ceria (CeO 2 ) is important to tailor the surface redox properties for a broad scope of applications. The emergence of high-entropy oxides (HEOs) has brought transformative opportunities for oxygen defect engineering in ceria yet has been hindered by the difficulty in controllably introducing transition metals to the bulk lattice of ceria. Here, we report the fabrication of ceria-based nanocrystals with surface-confined atomic HEO layers for enhanced catalysis. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Rost et al [5] reported the first HE oxide with a rock salt phase in 2015, which has led to the research of various crystalline phases (such as spinel [8] and perovskite [9] ). Several experiment studies have demonstrated that single-phase HE ceramics, with their excellent entropy-stabilized and semiconductor properties, can be effectively applied in the fields of energy storage, [10] catalysis, [11] thermoelectricity, [12] and wear-resistant coatings. [12] However, the poor interfacial polarization of single-phase ceramics significantly affects the wave-absorbing capability of HE oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Rost et al [5] reported the first HE oxide with a rock salt phase in 2015, which has led to the research of various crystalline phases (such as spinel [8] and perovskite [9] ). Several experiment studies have demonstrated that single-phase HE ceramics, with their excellent entropy-stabilized and semiconductor properties, can be effectively applied in the fields of energy storage, [10] catalysis, [11] thermoelectricity, [12] and wear-resistant coatings. [12] However, the poor interfacial polarization of single-phase ceramics significantly affects the wave-absorbing capability of HE oxides.…”
Section: Introductionmentioning
confidence: 99%
“…After transition metal doping, the single Co–N peak splits to multiple deconvoluted peaks for M-Co 3.75 N 0.14 samples which correspond to different M–N bond lengths. This indicates the increased disordering structure in the M-Co 3.75 N 0.14 lattice . The nearest Co–Co peak is located at ∼2.54 Å, while this Co–Co bond becomes shorter after transition metal doping.…”
Section: Resultsmentioning
confidence: 92%
“…This indicates the increased disordering structure in the M-Co 3.75 N 0.14 lattice. 27 The nearest Co−Co peak is located at ∼2.54 Å, while this Co−Co bond becomes shorter after transition metal doping. Based on the above structural analysis, it can be concluded that the doping of transition metal will cause structural defects and lattice distortion in M-Co 3.75 N 0.14 , which are beneficial for the formation of nitrogen vacancies (as active sites).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The lower onset temperature shows a lower energy barrier for lattice oxygen activation, which is ascribed to the high-entropy effect. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Discussionmentioning
confidence: 99%